(untitled) (Iraqi Journal of Medical Sciences, 2016)
In 1907, Siegfried Oberndorfer (1876–1944), a German pathologist at the University of Munich, coined the term karzinoide, or "carcinoma-like," to describe the unique feature of behaving like a benign tumor despite resembling a carcinoma microscopically. Carcinoid tumours are characteristically low grade malignant tumors with neuroendocrine differentiation that have been described in several locations, including the gastrointestinal, respiratory, hepatobiliary, and genitourinary systems. Carcinoid tumors most commonly occur in the gastrointestinal tract (74%) and bronchial system (25%). less than 1% of cases these tumors have been reported in the genitourinary system. In this report we describe a 55-year-old house wife female who presented with vague gastrointestinal complaints for long period then she developed intestinal obstruction due to small bowel carcinoid. The clinical findings are used to illustrate pathophysiology, classification, management of carcinoid tumours through review of literatures. Keywords: carcinoids tumours, neuroendocrine tumours, small bowel obstruction.